The extent of Libyan commercial banks’ commitment to social responsibility (A field study on the branches of commercial banks operating in the city of Sirte) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The social responsibility of economic institutions and organizations is of interest to many countries, as it is one of the means that contribute to achieving the well-being of society and improving it for the better. Given the increasing pressure on Libyan commercial banks to play their role towards the societal environment through their commitment to their social responsibilities, this study aimed to determine the extent of Libyan commercial banks’ commitment to that responsibility. To achieve this goal, a descriptive research approach and its known methods was adopted, where the field survey method was used for the purpose of collecting the data necessary to test the study hypotheses, through the use of a questionnaire form that was designed for this purpose. The study concluded by stating that the Libyan banks studied are committed to performing their social and environmental duties and also contribute to supporting most of the activities that support the movement of the economy, especially those related to developing the services of those branches. Therefore, the study recommended that the managements of Libyan commercial banks work to exert more effort towards social responsibility programs, including: Through increased focus on the cultural and social dimension, especially with regard to supporting sports activities and clubs.
Keywords: Social responsibility; dimensions of social responsibility; social responsibility in Libyan commercial banks